The Implementation of Accrual-based Accounting in Indonesian Government: Has Local Government Financial Statement Quality Improved? - Asaprima Putra Karunia; Payamta Payamta; Sutaryo Sutaryo (Journal of Accounting and Investment, 2019)
This paper seeks to find evidence accrual accounting implementation within local government in Indonesia. The evidence comes from the quality of financial statements published by the local government in Indonesia. The financial statements used in this study is financial statement publish from 2007 to 2016 by local government in Indonesia, including province, city, and regency. A total of 5,080 financial statements is used in this research. Based on the regulation, financial statements which published between 2007 and 2013 is published under Cash Toward Accrual accounting standard. Financial statements which published from 2014 onwards is using full accrual accounting standard. From those 5,080 financial statements, there is 3,515 financial statements publish using Cash Toward Accrual (CTA) basis, and 1,565 financial statements that using accrual basis. This research utilizes Mann-Whitney testing as an analysis technique. This research finds that accrual-based financial statements have a significant difference in total quality, relevance, reliability, and understandable value compared to CTA based financial statements. This research also finds that financial statement quality is improving every year. Although there has been an increase, those increase has not been maximized. Local governments must strive to improve the quality of their financial statements so that transparency and accountability delivered by local governments are maximized.